ASSESSMENT OF THE ULTIMATE STRAIN IN THE PROCESS OF THE TRANSVERSAL PRESSING OUT WITH FURTHER SETTLING - Sivak, Roman; Savuliak, Valeryi (Scientific Works of Vinnytsia National Technical University, 2024)
The paper considers the research of the metal plasticity in the process of the transversal pressing out of the axisymmetric flange with its further settling. The process is characterized by non-monotone loading. That is why, the calculation of the components of the stress deviator is carried out using the model of Backhouse anisotropic strengthening. As the known tensor models of the damages accumulation process at nonmonotone loading are cumbersome the transition from the tensor model to 3D scalar model is substantiated in the given paper. As the main characteristics of nonmonotone loading index of rigidity of the stress state and Nadai-Lode parameter are used. Instead of the six components of the damage tensor three components of damage deviator in the space of primary stresses are introduced. Function approximation is suggested, which describes the impact of the loading history on the plasticity and takes into account the sensitivity of the deformed metal to the scheme of the stress state. The impact of the stress state on the plasticity is determined by the surface of the ultimate strain, which describes the dependence of ultimate strain on two invariant indices of the stress state. Developed model of metal plasticity assessment at complex nonmonotone loading is used for the assessment of the impact of the parameters of the transversal pressing out of the flange on ultimate deformation. The suggested method of the combined pressing out enables to use rationally the resource of the plasticity of the deformed metal.